Development of universal integrated system of comparative rating of management companies in Russia - N. M. Kalinina; E. V. Khrapova; N. A. Kulik; S. V. Taruta (Омский научный вестник: Серия "Общество. История. Современность")
This article considers topical issues related to the conduct of comparative assessment of managing companies in the Russian Federation, in particular, it describes theoretical and methodological aspects of rating of managing companies in the sphere of provision of housing and communal services. During the study, the authors summarized and systematized existing methods of compiling ratings of management companies in Russia, identified «bottlenecks» that do not allow to obtain an objective assessment of the activities of management companies. The author’s methodology of comparative assessment of activities of managing companies in the sphere of provision of housing and communal services is proposed, based on selection and systematization of key evaluation criteria reflecting such aspects of activity as information openness of the managing organization to the population, quality of work with clients, financial condition of the managing company, additional criteria. The work describes the peculiarities of grouping of estimated parameters within each category and methods of their calculation. The results of testing of the methodology are given on the example of the management companies of Omsk